2021
DOI: 10.2174/1570159x19666210610092958
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Psychopharmacology in Borderline Personality Disorder

Abstract: Background: Patients with Borderline Personality Disorder (BPD) manifest affective and behavioural symptoms causing personal distress, relationship difficulties, and reduced quality of life with global functioning impairment, mainly when the disease takes an unfavourable course. A substantial amount of healthcare costs is dedicated to addressing these issues. Many BPD patients receive medications, mostly those who do not respond to psychological interventions. Objective: Our aim was to assess the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…However, some agents prove to be beneficial in several types of BPD symptoms, thus a symptom-targeted pharmacotherapy is a common strategy in clinical practice ( 50 ). Selective serotonin (SSRIs) and serotonin and norepinephrine (SNRI) reuptake inhibitors may be beneficial in reducing impulsivity, affective lability, irritability and somatic symptoms, although there is no conclusive evidence that they may contribute to consistent reduction of the severity of BPD ( 51 , 52 ). According to American Psychiatric Association (APA) guidelines, SSRI or SNRI should be a first-line pharmacological treatment of affective dysregulation and impulsive-behavioral dyscontrol symptoms in BPD ( 53 ).…”
Section: Current Bpd Treatment Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some agents prove to be beneficial in several types of BPD symptoms, thus a symptom-targeted pharmacotherapy is a common strategy in clinical practice ( 50 ). Selective serotonin (SSRIs) and serotonin and norepinephrine (SNRI) reuptake inhibitors may be beneficial in reducing impulsivity, affective lability, irritability and somatic symptoms, although there is no conclusive evidence that they may contribute to consistent reduction of the severity of BPD ( 51 , 52 ). According to American Psychiatric Association (APA) guidelines, SSRI or SNRI should be a first-line pharmacological treatment of affective dysregulation and impulsive-behavioral dyscontrol symptoms in BPD ( 53 ).…”
Section: Current Bpd Treatment Outlookmentioning
confidence: 99%
“…However, as APA guidelines indicate, mood stabilizers (lithium, valproate or carbamazepine) may be considered as a second-line or adjunctive treatment of symptoms within the above domains ( 53 ). Second generation antipsychotics have been reported to reduce anger, affective instability, impulsivity, paranoid ideation, dissociative symptoms and anxiety in BPD ( 52 ). APA guidelines recommend those particularly in treatment of cognitive-perceptual BPD symptoms, whereas The National Institute for Health and Care Excellence (NICE) guidelines state that antipsychotics can be considered only as a crisis treatment, prescribed for no longer than 1 week ( 54 ).…”
Section: Current Bpd Treatment Outlookmentioning
confidence: 99%
“…Indeed, the antisuicidal effect of lithium is well-known and was demonstrated to possibly rely on intrinsic properties of the molecule, independent from its efficacy as a mood stabilizer (Del Matto et al ., 2020). As for antiepileptic mood stabilizers, even if they do not appear to have direct antisuicidal properties (Wilkinson et al ., 2022), they could help in treating mood instability and impulsiveness, especially in subjects diagnosed with borderline personality disorders (Del Casale et al ., 2021), which was moderately prevalent in our sample. The reduction of antidepressant prescription rates from admission to discharge could be linked to the activating role attributed to these molecules, especially to SSRI, that is thought to potentially enhance suicidality-related phenomena in specific situations (Lagerberg et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with administration of monoamine reuptake inhibitors to healthy men showed that methylphenidate, which elevates DA and NE content in both the cortex and subcortical structures, increased the number of correct responses during the visual task, while atomoxetine, which mainly affects the frontal cortex, led to more impulsive reactions, and citalopram increased the number of missed stimuli [ 12 ]. The monoamines are involved in the implementation of impulsive and aggressive behavior, emotional instability, inhibitory control of these behavioral patterns, and a number of other symptoms of disorders associated with traumatic experiences [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Regional and gender specificity of 5-HT system activity in mediating such symptoms of BPD as impulsive aggression and emotional dysfunction were recently reported [ 14 , 18 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%